2020
DOI: 10.1002/csc2.20052
|View full text |Cite
|
Sign up to set email alerts
|

Predictive breeding for maize: Making use of molecular phenotypes, machine learning, and physiological crop models

Abstract: Maize (Zea mays L.) has been a focus of scientific research and breeding for over a century. It is also one of the most economically important crops in the world, with a value of approximately US$50 billion per year in the United States alone. Additionally, maize has long been the model species of choice for the study and exploitation of hybrid vigor, and it continues to be one of the world's most efficient converters of photosynthetic energy into starch. This review discusses the history and future of maize p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 138 publications
1
24
0
Order By: Relevance
“…A recent study in semi-winter rapeseed demonstrated that already low-density marker sets comprising a few hundred to thousand markers enable high prediction accuracies in breeding populations with strong LD (Werner et al 2018 ). As reviewed by Washburn et al ( 2020 ), key improvements of genomic prediction might come from high‐throughput phenotyping, the use of molecular phenotypes and/or component traits, machine learning methodologies, and replacing individual genetic markers with high‐quality haplotype data.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in semi-winter rapeseed demonstrated that already low-density marker sets comprising a few hundred to thousand markers enable high prediction accuracies in breeding populations with strong LD (Werner et al 2018 ). As reviewed by Washburn et al ( 2020 ), key improvements of genomic prediction might come from high‐throughput phenotyping, the use of molecular phenotypes and/or component traits, machine learning methodologies, and replacing individual genetic markers with high‐quality haplotype data.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, report that the performance of multi-trait and multi-environment deep learning (MTDL) is commensurate with that of the Bayesian multi-trait and multi-environment approach. Ersoz et al (2020) and Washburn et al (2020) review machine-learning approaches in crop improvement.…”
Section: Explaining and Simulating G × E × M Interactionsmentioning
confidence: 99%
“…Prediction of phenotypes from a combination of environmental (E), genetic (G), and humanimposed (often referred to as management(M)) conditions has been a long standing challenge in biology and related fields (Messina et al 2009(Messina et al , 2018Technow et al 2015;Cooper et al 2016Cooper et al , 2021Varshney et al 2017;Washburn et al 2020;Jarquin et al 2021;Li et al 2021).…”
Section: Introductionmentioning
confidence: 99%